Cost-utility and cost–benefit analysis of a multi-component intervention (NEXpro) for neck-related symptoms in Swiss office workers - Beatrice Brunner; Andrea Martina Aegerter; Venerina Johnston; Thomas Volken; Manja Deforth; Gisela Sjøgaard; Achim Elfering; Markus Melloh; the NEXpro Collaboration Group (BMC Public Health)
Abstract Background Neck pain is a significant public health issue, especially among office workers, with a prevalence ranging from 42 to 68%. This study aimed to evaluate the cost-utility and cost-benefit of a multi-component intervention targeting neck pain in the general population of office workers in Switzerland. The 12-week multi-component intervention consisted of neck exercises, health promotion information workshops, and workplace ergonomics sessions. Methods The study was designed as a stepped-wedge cluster randomized controlled trial and assessed using an employer’s perspective. The main analysis focused on the immediate post-intervention period. Long-term effects were examined in a subsample at the 4, 8, and 12-month follow-ups. The intervention effects on costs and quality-adjusted life years (QALYs) were estimated using generalized linear mixed-effects models, controlling for confounding factors. Incremental cost-effectiveness ratios (ICERs) and cost-effectiveness acceptability curves were presented, along with calculations of the break-even point and the return on investment. Various sensitivity analyses were performed. Results A total of 120 office workers participated in the trial, with 100 completing the intervention period and 94 completing the entire study. The main analysis included 392 observations. The intervention had a significant positive effect on QALYs and a nonsignificant effect on costs. The ICER was estimated at -25,325 per QALY gain, and the probability of the intervention being cost saving was estimated at 88%. The break-even point was reached one week after the end of the intervention. Conclusion The multi-component intervention is likely to reduce company costs and simultaneously improve the quality of life of employees. However, the implementation of such interventions critically depends on evidence of their cost-effectiveness. As there is still a large research gap in this area, future studies are needed. Trial registration ClinicalTrials.gov, NCT04169646 . Registered 15 November 2019-Retrospectively registered. Trial protocol Aegerter AM, Deforth M, Johnston V, Ernst MJ, Volken T, Luomajoki H, et al. On-site multi-component intervention to improve productivity and reduce the economic and personal burden of neck pain in Swiss office-workers (NEXpro): protocol for a cluster-randomized controlled trial. BMC Musculoskelet Disord. 2020;21(1):391.  https://doi.org/10.1186/s12891-020-03388-x .